2002
DOI: 10.1021/op010072q
|View full text |Cite
|
Sign up to set email alerts
|

Ceftibuten: Development of a Commercial Process Based on Cephalosporin C. Part IV. Pilot-Plant Scale Electrochemical Reduction of 3-Acetoxymethyl-7(R)-glutaroylaminoceph-3-em-4-carboxylic Acid 1(S)-Oxide

Abstract: This contribution describes the operation of a pilot plant for the production of 3-exomethylene-7(R)-glutaroylaminocepham-4-carboxylic acid 1(S)-oxide (4a) by the electrochemical reduction of 3-acetoxymethyl-7(R)-glutaroylaminoceph-3-em-4-carboxylic acid 1(S)-oxide (3a). This conversion is a key step in a new process for the production of Ceftibuten (1). The scale-up of the electrochemical reduction was demonstrated using a commercial flow-cell. The use of a novel type of extended-area tin cathode, which had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The use of a tin cathode was found to be optimal for this reaction; various reducible functionalities such as carboxylates, a β -lactam, and a sulfoxide were left unscathed. 666 …”
Section: Cathodic Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a tin cathode was found to be optimal for this reaction; various reducible functionalities such as carboxylates, a β -lactam, and a sulfoxide were left unscathed. 666 …”
Section: Cathodic Reductionmentioning
confidence: 99%
“…The use of a tin cathode was found to be optimal for this reaction; various reducible functionalities such as carboxylates, a β-lactam, and a sulfoxide were left unscathed. 666 The direct electrochemical reduction of aromatic systems is conceivably difficult owing to arenes' electron-rich nature. Nevertheless, early efforts demonstrated that electrochemical conditions could be utilized to generate solvated electrons which could, in turn, enable the Birch reduction of aromatic systems.…”
Section: Reduction Of Cc Double Bondsmentioning
confidence: 99%
“…Cathodic reduction of an allylic acetate as a key step in the synthesis of the antibiotic ceftibuten ( 214 ) was reported by Walker and coworkers (Scheme ) . The transformation was performed on large scale in a pilot‐plant using a flow‐cell setup.…”
Section: Cathodic Reductionmentioning
confidence: 99%
“…Reasonable rates of mass transport and good flow dispersion can be realised with this geometry, which also facilitates modular expansion and predictable scale-up [5,6]. The parallel plate cell configuration is widely used in many large-scale electrochemical processes, such as the production of chlorine and caustic soda, adiponitrile and pharmaceuticals [3,7,8].…”
Section: Introductionmentioning
confidence: 99%